Preparation of Carbon Nanosheet by Molten Salt Route and Its Application in Catalyzing VO2+/VO2+ Redox Reaction. Issue 6 (1st January 2019) - Lv, Yanrong; Zhang, Lu; Cheng, Gang; Wang, Pengfei; Zhang, Tianze; Li, Chuanchang; Jiang, Yingqiao; He, Zhangxing; Dai, Lei; Wang, Ling
Abstract : Carbon nanosheets were synthesized by facile molten salt route using glucose as carbon source, and employed as positive electrocatalyst for vanadium redox flow battery (VRFB). Two kinds of carbon nanosheets were obtained at glucose/salt mass ratio of 1:10 (CNS-10) and 1:100 (CNS-100), respectively. Compared with CNS-10, CNS-100 with graphene-like structure has crumpled shape and large surface area. Electrochemical measurements verify that as-prepared carbon nanosheets exhibit good electrocatalytic properties to VO 2+ /VO2 + redox reaction, and CNS-100 demonstrates the best performance. Excellent electrocatalytic performance of CNS-100 mainly comes from large specific area, crumpled shape and enhanced carbonization degree. These features favor the increase of reaction place, active site, and electrical conductivity, respectively, further accelerating the electrochemical kinetic process of VO 2+ /VO2 + redox reaction. The cell using CNS-100 as positive catalyst displays superior electrochemical performance. Higher discharge capacity and capacity retention can be achieved in the cell using CNS-100. Moreover, utilization of CNS-100 can lead to energy efficiency increase of 5.3% compared with pristine cell at 50 mA cm −2 . Low-cost, high-performance, and graphene-like nanosheet obtained by molten salt route offers a broad application prospect for VRFB.